Tangible User Interfaces in Computer Programming Learning: A Systematic Literature Review - Molina, Ana I.; Navarro, Christian X.; Alarcon, Oscar; Redondo, Miguel A. (IEEE access, 2025)
The teaching and learning of computer programming presents significant cognitive and pedagogical challenges, particularly for novice learners. In recent years, the use of Tangible User Interfaces (TUIs) has gained attention as a potentially promising approach for supporting programming education by enabling more intuitive, engaging, and hands-on learning experiences. This study presents a Systematic Literature Review (SLR) that synthesizes the current state of research on the integration of TUIs in programming instruction. The findings revealed that most studies employed tangible or graphical representations of programming constructs, often through metaphorical tasks. While these interactive and manipulative environments appear to support conceptual understanding and collaboration, a challenge is the limited integration and translation of block-based systems with text-based programming languages. This review indicates that TUIs may offer educational benefits including increased motivation, improved conceptual learning, and stronger collaborative dynamics. In addition, various challenges related to their implementation and effectiveness were highlighted and collected. The outcomes of this SLR provide valuable insights for educators, researchers, and developers of educational technologies and lay the foundation for future innovations in designing interactive learning environments that leverage physical interaction to enhance computer programming education.